Influence of diet complexity and weaning age on carcass characteristics and growth performance from weaning to market - T Signer; K Q Owen; R M Musser; J W Smith II; B T Richert; Steven S Dritz; Michael D Tokach; Robert D Goodband; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1994)
A total of 180 barrows (initially 7.4 or 11.9 lb and 9 or 19 d of age) was used in a growth assay to determine the influence of two weaning ages and three diet complexity sequences on growth performance and carcass characteristics. The growth performance of pigs used in this trial was excellent, as shown by the range of average age at 240 lb from 144 to 149.7 d. Growth performance was similar regardless of weaning age. Thus, when health status and environment are similar, pigs weaned at 19 d of age can attain a weight of 240 Ib at the same age as pigs weaned at 9 d of age. The three complexity sequences varied widely in diet composition and the length of time the complex diets were fed. The high complexity sequence was formulated to achieve maximal gain regardless of cost, the medium complexity sequence was formulated to closely match current Kansas State University recommendations, and the low complexity diets were very simple diets with minimal amounts of alternative ingredients fed for short periods of time. Pigs performed the best on the high or medium sequence in Phase I post-weaning. However, growth performance of pigs fed the simple sequence was similar to that of pigs in the medium or high sequences for the 15 to 40 Ib phase. Thus, the data tend to indicate that diet complexity is critical in the first week postweaning, but the complexity can be decreased rapidly for feeding high health-status pigs without reducing performance. This experiment illustrates the tremendous growth potential of the high health-status pigs and that similar growth and performance can be achieved from pigs weaned at 9 and 19 d of age.; Swine Day, Manhattan, KS, November 17, 1994
Keywords: Swine day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-175-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 717; Swine; Starter pig; Diet complexity; Growth